2009
DOI: 10.1021/jm900756t
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and In Vitro Opioid Receptor Functional Antagonism of Methyl-Substituted Analogues of (3R)-7-Hydroxy-N-[(1S)-1-{[(3R,4R)-4-(3-hydroxyphenyl)-3,4-dimethyl-1-piperidinyl]methyl}-2-methylpropyl]-1,2,3,4-tetrahydro-3-isoquinolinecarboxamide (JDTic)

Abstract: In previous structure–activity relationship (SAR) studies, (3R)-7-hydroxy-N-[(1S)-1-{[(3R,4R)-4-(3-hydroxyphenyl)-3,4-dimethyl-1-piperidinyl]methyl}-2-methylpropyl]-1,2,3,4-tetrahydro-3-isoquinolinecarboxamide (JDTic, 3) was identified as the first potent and selective κ-opioid receptor antagonist from the trans-3,4-dimethyl-4-(3-hydroxyphenyl)piperidine class of opioid antagonists. In the present study, we report the synthesis of analogues 8a–p of 3 and present their in vitro opioid receptor functional antago… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 33 publications
1
23
0
Order By: Relevance
“…To assess the validity and generality of the hypothesis that long duration of antagonism was a consequence of JNK activation, we examined the properties of this wide range of available ligands reported to produce selective -opioid antagonism (Portoghese et al, 1987;Carroll et al, 2004Carroll et al, , 2006Cueva et al, 2009;Grimwood et al, 2011). In this analysis, we find that for 12 structurally different -antagonists, stimulation of phospho-JNK-immunoreactivity (ir), in spinal cords of antagonist-injected mice and in KOPr-transfected HEK293 cells treated with antagonist in vitro, is strongly correlated with in vivo duration of antagonism of U50,488-induced analgesia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To assess the validity and generality of the hypothesis that long duration of antagonism was a consequence of JNK activation, we examined the properties of this wide range of available ligands reported to produce selective -opioid antagonism (Portoghese et al, 1987;Carroll et al, 2004Carroll et al, , 2006Cueva et al, 2009;Grimwood et al, 2011). In this analysis, we find that for 12 structurally different -antagonists, stimulation of phospho-JNK-immunoreactivity (ir), in spinal cords of antagonist-injected mice and in KOPr-transfected HEK293 cells treated with antagonist in vitro, is strongly correlated with in vivo duration of antagonism of U50,488-induced analgesia.…”
Section: Introductionmentioning
confidence: 99%
“…at ASPET Journals on May 13, 2018 molpharm.aspetjournals.org Cueva et al, 2009;Beardsley et al, 2010). The diaryl ethers include FP3FBZ [(S)-3-fluoro-4-(4-((2-(3-fluorophenyl)pyrrolidin-1-yl)methyl)phenoxy)benzamide] ; JSPA0658 [(S)-3-fluoro-4-(4-((2-(3,5-dimethylphenyl)pyrrolidin-1-yl)methyl)phenoxy)benzamide] [previously referred to as LY-DMPF (Peters et al, 2011); also known as LY2456302 (Buezo et al, 2010)]; and JSPA071B, [(S)-3-fluoro-4-(4-((2-(3,5-bis(trifluoromethyl)phenyl)pyrrolidin-1-yl)methyl)phenoxy)benzamide].…”
mentioning
confidence: 99%
“…In a study conducted at RTI, JDTic was found to have K e = 0.02 nM and was 1255- and 3830-fold selective for the κ receptor relative to the μ and δ opioid receptors, respectively (Table 11). [33] For comparison, nor-BNI had K e = 0.04 and 0.05 nM in the OTDP and RTI studies and was 475- and 115-fold (OTDP study) and 520- and 580-fold (RTI study) selective for the κ relative to the μ and δ opioid receptors, respectively. [31, 33] In a study conducted at Lilly Research Laboratories, JDTic had a K e value of 0.098 nM and was 67- and 1718-fold selective for the κ relative to the μ and δ opioid receptors, respectively.…”
Section: Discovery Of Jdticmentioning
confidence: 99%
“…[33] For comparison, nor-BNI had K e = 0.04 and 0.05 nM in the OTDP and RTI studies and was 475- and 115-fold (OTDP study) and 520- and 580-fold (RTI study) selective for the κ relative to the μ and δ opioid receptors, respectively. [31, 33] In a study conducted at Lilly Research Laboratories, JDTic had a K e value of 0.098 nM and was 67- and 1718-fold selective for the κ relative to the μ and δ opioid receptors, respectively. [34] In comparison, nor-BNI had K e = 0.80 nM and 41-and 18-fold selectivity for the κ relative to the μ and δ opioid receptors, respectively (Table 11).…”
Section: Discovery Of Jdticmentioning
confidence: 99%
“…Even though compound 37 possesses druglike properties and performed well in several animal behavioral tests [21][22][23], medicinal chemists still endeavored to pursue analogues which could have better pharmacokinetic properties and ability to penetrate the blood-brain barrier [24][25][26]. Compounds 38-42 were the promising JDTic analogues with ideal calculated logBB which suggested they would possess better blood-brain barrier penetration than compound 37 [26]. Among them, compound 42 was the most potent analogue with K e value of 0.03 nM for the receptor and 120-and 28000-fold selective relative to the μ and opioid receptors.…”
Section: -Opioid Receptor Antagonistsmentioning
confidence: 99%